Daily-life affective instability in emotional distress disorders is associated with function and structure of posterior parietal cortex. (29th February 2020) - Hua, Jessica P.Y.; Trull, Timothy J.; Merrill, Anne M.; McCarty, Riley M.; Straub, Kelsey T.; Kerns, John G.
Highlights: Examined neural-affective instability associations in emotional distress disorders. Used a multimodal neuroimaging and ambulatory assessment approach. Posterior parietal cortex is an attentional control/emotion regulation area. Affective instability and decreased activation of left posterior parietal cortex. Affective instability and hypogyria of left posterior parietal cortex. Abstract: Affective instability (i.e., large and frequent shifts in negative emotions) is a key emotion dysregulation symptom in emotional distress disorders and can be reliably and validly assessed using ambulatory assessment. However, no study has examined whether affective instability is associated with brain function and structure. Using multimodal neuroimaging and ambulatory assessment, we examined associations between functional activation and cortical structure with ambulatory-assessed affective instability in emotional distress disorders ( n  = 27). Increased daily life-affective instability was associated with decreased neural activation on an emotion regulation task in a left inferior parietal region consistently associated with emotion regulation. Daily-life affective instability was also associated with hypogyria in this same left inferior parietal region, with hypogyria extending into additional posterior parietal regions. This study found evidence that daily-life affective instability was associated with both functionstructure of the posterior parietal cortex, a key attentional control region involved in emotion regulation.